Global Distribution of Shigella sonnei Clones - Filliol-Toutain, I.; Chiou, C.S.; Mammina, C.; Gerner-Smidt, P.; Thong, Kwai Lin; Phung, D.C.; Pichel, M.; Ranjbar, R.; Sow, A.G.; Cooper, K.; Ribot, E.; Binsztein, N.; et al. (2011)
To investigate global epidemiology of Shigella sonnei, we performed multilocus variable number tandem repeat analysis of 1,672 isolates obtained since 1943 from 50 countries on 5 continents and the Pacific region. Three major clonal groups were identified; 2 were globally spread. Type 18 and its derivatives have circulated worldwide in recent decades.